2017
DOI: 10.18632/oncotarget.14632
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of intratumoral CD103+ tumor-infiltrating lymphocytes in pulmonary squamous cell carcinoma

Abstract: CD103 is the αE subunit of αEβ7 integrin that is expressed in tissue-resident memory T cells, where it promotes cytotoxic T cell responses against tumors. However, little is known about its expression or clinicopathological implications in non-small cell lung cancer (NSCLC). This study investigated the prognostic implications of CD103+ tumor-infiltrating lymphocytes (TILs) in NSCLC. We established two cohorts: patients with resected NSCLC (n = 132) and patients with pulmonary squamous cell carcinoma (pSCC), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
54
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 33 publications
7
54
1
Order By: Relevance
“…Ultimately, they found that patients with tumors containing a high density of CD103+ CD8+ T RM cells had significantly better survival than those with tumors containing a low density of CD103+ CD8+ T RM cells. Likewise, two other recent studies have demonstrated a similar link between CD103+ CD8+ T RM cells and patient prognosis in lung cancer (8,9). These survival findings further implicate tumor-infiltrating T cell responses as a crucial component of the tumor-immune microenvironment and identify a unique subset of T cells, CD103+ CD8+ T RM cells, which are likely responsible for the previously reported survival outcomes linked to tumor-infiltrating T cell densities.…”
supporting
confidence: 73%
“…Ultimately, they found that patients with tumors containing a high density of CD103+ CD8+ T RM cells had significantly better survival than those with tumors containing a low density of CD103+ CD8+ T RM cells. Likewise, two other recent studies have demonstrated a similar link between CD103+ CD8+ T RM cells and patient prognosis in lung cancer (8,9). These survival findings further implicate tumor-infiltrating T cell responses as a crucial component of the tumor-immune microenvironment and identify a unique subset of T cells, CD103+ CD8+ T RM cells, which are likely responsible for the previously reported survival outcomes linked to tumor-infiltrating T cell densities.…”
supporting
confidence: 73%
“…Studies analyzing the infiltration of T RM cells in human tumors have shed some light on their relevance in anti‐tumor immunity. Tumor infiltration of CD8 + T cells exhibiting a resident phenotype (CD69 + CD103 + and/or CD103 + ) correlates with a more favorable prognosis for various human cancers (Djenidi et al, ; Koh et al, ; Wang et al, ; Webb, Milne, Watson, Deleeuw, & Nelson, ). Similar correlations were shown for human melanoma (Edwards et al, ; Murray et al, ) (Figure ).…”
Section: Skin‐resident T‐cell Responses In Melanomamentioning
confidence: 99%
“…PD-1 expression in lymphocytes was evaluated intratumourally, based on the number of positive TILs counted in three high-power fields (HPF) (400-fold magnification) of highest density. Stratification was made for negative expression (0-5), weak (6)(7)(8)(9)(10)(11)(12)(13)(14)(15), moderate (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) or strong (>30) infiltration patterns.…”
Section: E V a L U A T I O N O F I M M U N O H I S T O C H E M I C A mentioning
confidence: 99%
“…The prognostic significance of TILs has been evaluated in several malignancies, including breast cancer, non-small-cell lung cancer and oesophageal squamous cell carcinoma, revealing better clinical outcome when high levels of TILs are present. [6][7][8] In HNSCC, high levels of TILs are associated with favourable patient survival. [9][10][11][12] However, studies focusing on the prognostic relevance of PD-1-expressing TILs in HNSCC are sparse.…”
Section: Introductionmentioning
confidence: 99%